ASAS KEADILAN PELAKSANAAN PEMUTUSAN HUBUNGAN KERJA (PHK) ATAS TUNGGAKAN UPAH KARYAWAN PT. SARANA PARIWARA(Studi Kasus Putusan Nomor 46/Pdt.Sus-PHI/2021/PN.SMg) - Monica Apriyanti (2024)
In the provision of wages, there are still several companies that often fail to fulfill their obligations as employers, namely by not providing wages or delaying the payment of wages to employees, as was the case with employees of PT. Sarana Pariwara, leading them to file a Termination of Employment Lawsuit through the litigation route, namely the Industrial Relations Court. The issues addressed are: What are the considerations of the judge regarding the wage arrears lawsuit by employees of PT. Sarana Pariwara in Decision No. 46/Pdt.Sus-PHI/2021/PN.SMg? How does the Principle of Justice Implementation contribute to the resolution of Industrial Relations Disputes that ensures justice for PT Sarana Pariwara employees? To address these issues, a normative juridical research approach was conducted using secondary data as the primary source related to the research object. The analytical approach used was qualitative descriptive. The conclusions of this research are as follows: (1) Considerations by the judge regarding the Termination of Employment and its legal consequences are based on Law No. 13 of 2003 concerning Manpower; (2) the principle of justice should ensure full payment in accordance with the decision of the Industrial Relations Court or take legal execution steps, such as filing an execution seizure and bankruptcy petition against PT. Sarana Pariwara.